Confucianism and Social Issues in China - the Academician Kang Xiaoguang. Investigations into NGOs in China, the Falun Gong, Chinese Reportage, and the Confucian Tradition. - Gänßbauer, Monika (Projekt Verlag, 2011)
Kang Xiaoguang, b. 1963, is a prominent academic and an independent thinker in mainland China. He once served as an advisor to Premier Zhu Rongji. Since the early 2000s Kang has been an ardent advocate of Confucianism and of the establishment of Confucianism as China's state religion. His books, however, cover a broad range of other topics, too. This publication offers the first book-length introduction into and discussion of topics and content of Kang's work. Kang Xiaoguang is a prolific scholar dealing with rural development in China and NGO project work and has also done extensive research on the religious movement Falun Gong, which he sees as an important agent for China's modernization. Another study he did is a piece of reportage literature. Here Kang looks into the case of Li Siyi, the death of a 3-year-old child and the failure of individuals and societal agents to prevent the tragedy. This study also collects together responses to Kang Xiaoguang's various theses from other authors belonging to the Chinese-speaking world.–Publisher's description.